2006
DOI: 10.1093/ije/dyl043
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the causes of 4 million neonatal deaths in the year 2000

Abstract: This exercise highlights the lack of reliable cause-of-death data in the settings in which most neonatal deaths occur. Complex statistical models are not a panacea. Representative data with comparable case definitions and consistent hierarchical cause-of-death attribution are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
339
3
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(365 citation statements)
references
References 44 publications
15
339
3
8
Order By: Relevance
“…In view of these differences, the data for cause of death presented here are based on South Africa's national burden of disease study [33] and [36] with use of population-based proportionate data for cause of death from 1996, updated for 2000, and revised to use programmatically relevant causes of death categories in the neonatal period rather than the perinatal causes. [37] and [38] Neonatal causes, childhood infections such as pneumonia and diarrhoea, and HIV/AIDS each account for roughly 30% of all child deaths. Deaths during the first month of life, the time of highest risk for child death, are due to three main causes: infections, complications of preterm birth, and birth asphyxia.…”
Section: Figure 2 Cause Of Death In South Africamentioning
confidence: 99%
“…In view of these differences, the data for cause of death presented here are based on South Africa's national burden of disease study [33] and [36] with use of population-based proportionate data for cause of death from 1996, updated for 2000, and revised to use programmatically relevant causes of death categories in the neonatal period rather than the perinatal causes. [37] and [38] Neonatal causes, childhood infections such as pneumonia and diarrhoea, and HIV/AIDS each account for roughly 30% of all child deaths. Deaths during the first month of life, the time of highest risk for child death, are due to three main causes: infections, complications of preterm birth, and birth asphyxia.…”
Section: Figure 2 Cause Of Death In South Africamentioning
confidence: 99%
“…The Child Health Epidemiology Research Group (CHERG) has identified a commonly used hierarchy (congenital abnormality-neonatal tetanus-preterm-birth asphyxia-sepsis/pneumoniadiarrhea-other) to estimate the cause distribution of neonatal deaths. 36 Conditions like congenital malformation and neonatal tetanus with highly specific symptoms (for example malformation, for the former and spasms, stiff neck and jaw for the latter) can be diagnosed by VA with reasonable certainty 16 and are therefore often placed high in the hierarchy. As each cause of death is identified, cases assigned to the cause are sequentially removed from the sample and cannot be assigned another cause of death.…”
Section: Va Cause Of Death Assignmentmentioning
confidence: 99%
“…Currently, there are six recognized direct causes of neonatal deaths identifiable by VA: (1) serious infection (including sepsis, pneumonia), (2) birth asphyxia, (3) prematurity, (4) tetanus, (5) congenital malformation and (6) diarrhea. 36,45 The ICD-10 specifies the listing of the following information on causes of death on the standard International Form of Medical Certification of Death: 46 (1) disease or condition directly leading to death, generally known as the direct cause of death, (2) antecedent causes (morbid conditions, if any, giving rise to the direct cause), otherwise known as the underlying cause(s), and (3) other significant conditions contributing to the death, but not related to the disease or conditions causing it, also known as the contributory cause(s). 47 These definitions can be difficult to interpret when we consider causes of neonatal death.…”
Section: Lack Of Standardized Death Classification Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include Eberstein et al (1990), who used eight categorical and continuous independent variables, including marital status, education, and birth weight, to model five infant cause-specific mortality rates. Lawn et al (2006) applied the multinomial logistic framework to model the distribution of neonatal deaths in countries with poor data; see Johnson et al (2010) and Liu et al (2012) for related work. Bradshaw et al (2003) and Shahraz et al (2012) employed a multinomial model to redistribute unknown or ill-defined deaths; see Murray et al (2006) for a related application to ill-defined causes.…”
Section: Introductionmentioning
confidence: 99%